"It's not who I am": Children's experiences of growing up with a long‐term condition in England, Australia, and New Zealand. Issue 4 (26th September 2017) - Carter, Bernie; Ford, Karen; Bray, Lucy; Water, Tineke; Arnott, Janine; Tichanow, Cassandra; Dickinson, Annette
Abstract: Purpose: Most studies of growing up with a long‐term condition focus on older children and adolescents and are condition‐specific. Relatively few studies address the experiences of children in middle childhood or consider their experience across a range of conditions, countries, and health settings. This study aimed to explore children's perceptions and understandings of how their lives are shaped (or not) by a long‐term condition and its associated management. Design and methods: A qualitative, participatory methodology using autodriven photoelicitation interviews (PEIs) with 45 purposively recruited children (6–12 years) with long‐term conditions (e.g., hemophilia, arthritis, Crohn's disease), from England, New Zealand, and Australia was utilized. PEI facilitated the construction of inductively derived understandings of the children's experiences as the children had control over creating and then selecting which photographs to discuss with the researcher. Results: Interpretive thematic analysis of the interviews and content analysis of the photographs resulted in an overarching theme, "It's not who I am …" but it is part of me, and three subthemes: getting on with my life; the special value of family, friendship, support, and comfort; and things that get in the way of getting on. Across all ages and the three countries, the children actively projected their self‐concept as "well" children and they strove, through their photographs and their accompanying explanations of their lives, to emphasize that they were "normal" children. They were active social agents who demonstrated their capacity to shape parts of their lives interdependently with their parents and the requirements of their condition. Practice implications: Pediatric nurses should be aware of the importance that children with long‐term conditions place on projecting and protecting their sense of being normal and ensure that when they engage with children that they take account of the children's understandings and efforts to live a life constrained but not limited by the condition.